USE OF DIGITAL MEDIA DURING THE COVID-19 PANDEMIC: SURVEY EXPLANATORY THE INFLUENCE OF ZOOM MEETING MEDIA TO SATISFACTION STUDENT - Larasati, Nabila; Atmaja, Suhendra; Anggraini, Ine (Jurnal Komunikasi dan Bisnis, 2023)
The industrial era 4.0 had a major influence on the communication process during the COVID-19 pandemic, especially in the field of education, in the learning process carried out online or online using the Zoom meeting media application . The purpose of this research is to find out how strong the effect of zoom meeting media is on student satisfaction. Researchers provide research limitations for digital media using only zoom meeting media. The theory used in this research is media zoom meetings with the dimensions of duration, frequency, media orientation, media access and media control. This research is a quantitative research. Data collection was taken by nonprobability sampling method using purposive sampling technique. The sample used in this study were 83 respondents. The method of analysis in this study is statistical analysis and the SPSS program used for processing. The results of the study show that there is a positive and significant influence between the influence of zoom meeting media on student satisfaction with a moderate level of influence.